A field perspective on effects of fire and temperature fluctuation on Cerrado legume seeds. Issue 2 (3rd April 2017) - Daibes, L. Felipe; Zupo, Talita; Silveira, Fernando A.O.; Fidelis, Alessandra
Abstract: Information from a field perspective on temperature thresholds related to physical dormancy (PY) alleviation and seed resistance to high temperatures of fire is crucial to disentangle fire- and non-fire-related germination cues. We investigated seed germination and survival of four leguminous species from a frequently burned open Neotropical savanna in Central Brazil. Three field experiments were conducted according to seed location in/on the soil: (1) fire effects on exposed seeds; (2) fire effects on buried seeds; and (3) effects of temperature fluctuations on exposed seeds in gaps and shaded microsites in vegetation. After field treatments, seeds were tested for germination in the laboratory, together with the control (non-treated seeds). Fire effects on exposed seeds decreased viability in all species. However, germination of buried Mimosa leiocephala seeds was enhanced by fire in an increased fuel load treatment, in which we doubled the amount of above-ground biomass. Germination of two species ( M. leiocephala and Harpalyce brasiliana ) was enhanced with temperature fluctuation in gaps, but this condition also decreased seed viability. Our main conclusions are: (1) most seeds died when exposed directly to fire; (2) PY could be alleviated during hotter fires when seeds were buried in the soil; and (3) daily temperature fluctuations in gaps also broke PY of seeds on the soil surface, so many seeds could be recruited or die before being incorporated into the soil seed banks. Thus seed dormancy-break and germination of legumes from Cerrado open savannas seem to be driven by both fire and temperature fluctuations.